Traditional Japanese herbal medicines for treatment of odontopathy - Yamaguchi, Kojiro (Frontiers in Pharmacology, 2015)
This article highlights several refractory oral diseases, such as stomatitis, burning mouth syndrome (BMS), glossalgia, atypical facial pain (AFP), oral cancer, dry mouth, and Sjögren's syndrome (SJS), in which use of Japanese herbal medicines, Kampo medicines (KM), on the basis of Kampo theory could exert the maximum effects on human body. (1) In acute stomatitis, heat because of agitated vital energy may affect the head, chest, and middle abdominal region. Stomatitis is also related to the generation of reactive oxygen species (ROS). There are many antioxidants in the crude extracts of KM. Thus, we can control environmental factors (cold, heat, dampness, dryness) and vital energy, blood, and fluid of the organ systemically using KM to treat stomatitis and eliminate local ROS accumulation. (2) BMS, glossalgia, and AFP are multifactorial syndromes involving the interaction of biological and psychological factors. Local temperature decrease and edema often occur in chronic pain. These are local circulatory disturbances that can be resolved by improving the flow of blood and fluid. Several KM, such as Tokishakuyakusan and Kamishoyosan (KSS), are effective for enhancing peripheral circulation. Those such as Saikokaryukotuboreito, Yokukansan, KSS, and Saibokutou can reduce stress and associated pain by altering glutamatergic and monoaminergic transmission in the brain. The clinical efficacy of KM for BMS and AFP may depend on the regulation of the mesolimbic dopaminergic and descending glutamatergic pain modulation systems. (3) Regarding oral cancer treatment, I introduce four possible applications of KM, inhibition of the proliferation of cancer cells, complementation of the main cancer therapy, reduction of side effect caused by the main anti-cancer therapy and improvement of quality of life such as the overall status and/or oral discomfort. This review explains in more details Hozai such as Hochuekkito (HET), Juzendaihoto, and Ninjinyoeito (NYT) that are frequently used to improve both immunosuppression and deficiencies of Ki, Ketsu, and Sui in oral cancer patients. (4) Heat- and cold-dryness stages exist in dry mouth and SJS. Byakkokaninjinto is useful for heat-dryness, while NYT, Bakumondoto, and HET have moisturizing effects in the cold-dryness stage. Thus, Kampo therapy is useful for many oral diseases that cannot be cured by western medicine.